A theoretical investigation of light scattering in chiral nematic liquid crystals - Hunte, Carlos (2008)
Summary: Using the Landau-de Gennes theory of short-range orientational order in the isotropic phase, closed-form expressions for the temperature dependence of the scattered intensity of chiral nematic liquid crystals are derived. Detailed calculations are included and the results are expressed in a form that can be easily tested experimentally
Bibliografija: 7 jed
Sažetak
Keywords: Tekući kristali -- Optička svojstva; Polarizacija svjetlosti -- Mjerenje; Polarizacija svjetlosti -- Matematičke metode